The teaching of physics at upper secondary school level: A comparative study between Indonesia and Ireland - Sudirman, Sudirman; Kennedy, Declan; Soeharto, Soeharto (Frontiers in Education, 2023)
This study aims to investigate the teaching approaches taken by physics teachers in Indonesia and Ireland when teaching a module on Medical Physics in the classroom. Additionally, students' attitudes to the module on Medical Physics were also explored. In particular, the views of these teachers towards Inquiry Based Science Education and Direct Instruction when implementing this module with students in the 14 - 16 age group were examined. Data were collected to investigate how teachers in the two countries used combinations of the IBSE and DI teaching approaches when teaching the module to their students. Arising out of the implementation of the module, it was hoped that the module would serve as a "hook" to interest students in physics by teaching topics in physics via real-life applications of physics. Thus, the attitudes of the students towards science on completion of the module were assessed. A total of 15 schools in Indonesia (402 students) and 15 schools in Ireland (263 students) participated in the project. Data were collected from the teachers and students using questionnaires. Among the findings were that whilst teachers in Ireland were unanimous in their agreement with the inclusion of IBSE activities in the lesson plans supplied, only 67% of the teachers in Indonesia agreed with the inclusion of these activities in the module. There was a strong relationship between the type of school and the students’ attitude towards the module. Students in the more academic type schools in both Ireland and Indonesia were less positive about the module. Among the problems highlighted by teachers in Indonesia was the lack of laboratory facilities. Also, students in both countries commented on the problems with terminology and literacy in general when studying physics. Whilst the module brought out a positive response from students convincing them to continue with their study of physics at the upper secondary school level.